Potentiometric and spectroscopic studies of the complex formation in the 6-methyl-2-thiouracil and copper(ii) ion system. (1st September 2022) - Skrobanska, Monika; Zabiszak, Michal; Taras-Goslinska, Katarzyna; Nowak, Martyna; Kaczmarek, Malgorzata T.; Frymark, Justyna; Michalska, Danuta; Jastrzab, Renata
Graphical abstract: The complexes of copper(ii ) ions with 6-methyl-2-thiouracil were investigated as well as in liquid and the solid-state. The spectroscopic, microstructural and theoretical studies of obtained complexes were performed. The sizes of obtained powders were around 5–15 µm. Abstract: New complexes of 6-methyl-2-thiouracil (L) with copper(ii ) ions were investigated. The studies were performed in relatively low concentrations in aqueous solutions that allowed the formation of solubility complexes. Hydroxo complexes were detected and characterized for the first time, as well as the influence of the metal ion:ligand concentration ratio on the distribution of forms and the fluorescent properties was demonstrated. Analysis was performed using a potentiometric method with computer analysis of the data and electron paramagnetic resonance, Vis, and fluorescence spectroscopy. The overall stability constants of the complexes were calculated. Analysis of the equilibrium constants as well as spectroscopic data and theoretical calculations allowed us to determine the type of coordination in the complexes found in the studied system.